The Influence of Profitability, Firm Size and Leverage on Income Smooting (Studies on Property and Real Estate Company on The Indonesia Stock Exchange 2012-2017) - Yuniar Aemanah S; Deannes Isynuwardhana (Universitas Islam Bandung, 2019)
Income smoothing is one of the strategies or business conducted by the company's management with the aim to reduce the fluctuations in earnings This is done with the motivation to show good performance to investors. This effort is made by playing with the income and the cost of the current period to be higher or lower than the actual income and expenses. Income smoothing is one form of earnings management. This study aims to determine the effect of independent variables in the form of profitability, firm size, and leverage to the practice of income smoothing in property and real estate companies listed on the Indonesia Stock Exchange 2012 to 2017. The method used in sampling this study using purposive sampling which produces 23 samples within the period of 6 (six years) of 138 sample units. The analytical method used is logistic regression analysis processed using SPSS 23. Based on the result of research, it is found that simultaneously profitability, firm size, and leverage variables influence the practice of income smoothing. Partially variable of firm size, and leverage do not have an effect on income smoothing, while profitability variable have positive and significant effect to income smoothing.